1993
DOI: 10.1002/app.1993.070490901
|View full text |Cite
|
Sign up to set email alerts
|

On the critical molecular chain length of polydimethylsiloxane

Abstract: SYNOPSISBecause a study of the results reported for the chain dimensions of polydimethylsiloxane (PDMS) , critical for the onset of this polymer's non-Newtonian flow behavior, obtained from the viscosity-molecular weight relationships available from the literature, clearly revealed that considerable differences exist between the reported data, a detailed analysis of these data was performed together with an additional examination of 10 new PDMS samples that were selected so as to have molecular weights that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
5
30
1
Order By: Relevance
“…Polydimethylsiloxanes (PDMSs) have good electrical properties, low surface energy, the ability to withstand damage, resistance to contamination and very low glass transition temperatures of the order of − 123 °C. Their low surface tension, low solubility and low dielectric constant are due to chain flexibility and weak intermolecular forces 1–3. They are used in making high‐voltage insulators as well as coatings on porcelain and glass in order to improve the hydrophobic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Polydimethylsiloxanes (PDMSs) have good electrical properties, low surface energy, the ability to withstand damage, resistance to contamination and very low glass transition temperatures of the order of − 123 °C. Their low surface tension, low solubility and low dielectric constant are due to chain flexibility and weak intermolecular forces 1–3. They are used in making high‐voltage insulators as well as coatings on porcelain and glass in order to improve the hydrophobic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the high-molecular-weight sample exhibits a bi-exponential decay, clearly showing heterogeneity of the molecular motion, which is explained by the presence of entanglements. The molecular weight is well above the reported entanglement molecular weight of PDMS of about 35,000 g/mol [17]. Entanglements of the polymers leads to restricted motion and thus less averaging of the dipolar coupling and, therefore, shorter T 2 .…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, the zero-shear viscosity ( η 0 ), determined as the complex viscosity ( η *) at low shear-rates ( Figure S7 ), is much higher (47,300 Pa·s) compared to that of the free-flowing parent vinyl-terminated PDMS (0.1 Pa·s). Remarkably, the molecular weight of the PDMS-PY employed in this study ( M n = 9620 Da) was well below the critical molecular weight of PDMS (reported at M c = 34,500 Da, approximate DP > 400, [ 45 ]); therefore, we can postulate that the rheological observations are not due to the entanglement of the linear PDMS chains, but mostly due to the reversible crosslinks between the PDMS/PS in the form of Lewis pairs.…”
Section: Resultsmentioning
confidence: 79%